Corrosion Rate Analysis Under Coating and Temperature Variations: Analisis Laju Korosi pada Lapisan Pelindung dan Variasi Suhu - Harun, Bagus Mulya; Mulyadi (Indonesian Journal of Innovation Studies, 2025)
General Background: Corrosion is a critical issue affecting the durability and performance of metallic materials in industrial environments. Specific Background: Variations in coating type and temperature conditions can alter the corrosion behavior of metal surfaces, leading to differences in degradation rates. Knowledge Gap: Previous studies have not consistently examined the combined role of coating variations and temperature conditions in determining corrosion characteristics under controlled testing environments. Aims: This study aims to analyze corrosion rate behavior under different coating types and temperature variations to identify dominant factors influencing material degradation. Results: Experimental findings show that variations in coating type and temperature produce different corrosion rates, where certain coatings demonstrate better resistance under specific thermal conditions. The analysis highlights measurable differences in corrosion performance across tested samples. Novelty: This study provides a focused evaluation of combined coating and temperature variables in corrosion testing, offering a comparative perspective on material resistance. Implications: The results support material selection and protective coating strategies to improve durability and reduce degradation risks in industrial applications. Keywords: Corrosion Rate, Coating Variation, Temperature Effect, Material Degradation, Protective Layer Key Findings Highlights Coating types produce distinct degradation patterns under testing conditions Thermal variation alters material surface response significantly Experimental comparison reveals dominant degradation factors